L'émancipation des femmes Madare : l'impact du projet administratif et missionnaire sur une société africaine, 1900-1960 - Doti-Sanou, Bruno. (Studies in Christian Mission, 1994)
This work is concerned with the civil authorities' and missionaries' project of the emancipation of Madarε women in the west of Burkina Faso between 1900 and 1960. The work deals successively with the place of women in the pre-colonial village community, the beginning of contacts with European civilisation, the project's initiators' assessment of the women's living conditions and their willingness to change them, the means and methods used to this end and the limitations of the project at the time of independence in 1960. The fruit of several years of research by a historian, who is a member of the ethnic community, this work is a documentary reference work with multiple entries and an index. It will be of interest to Africans concerned with the socio-political evolution of their continent, researchers interested in the history of missions and the African churches, and anyone concerned with the whole question of women in modern societies.